Grain yield, adaptability and stability of soybean genotypes in different Cerrado environments of Piauí, Brazil - De Alcântara Neto, Francisco; De Oliveira Tavares, Silvana; De Sousa Leite, Wallace [UNESP]; Da Silva, José Algaci Lopes; Filho, Carlos Humberto Aires Matos; De Amaral Gravina, Geraldo (Lepidus Tecnologia, 2018)
The objective of the present study was to evaluate the grain yield and the phenotypic adaptability and stability of soybean genotypes in different Cerrado environments of Piauí, Brazil, to provide indications for cultivation in the region. Therefore, we evaluated 23 soybean genotypes and three checks in three different site (Bom Jesus-PI, Monte Alegre-PI and Currais-PI) and environments (crop year 2010/11, 2011/12 and 2012/13). Experiments were carried out in a randomized complete block design with four replications. The behavior for the average grain yield of genotypes within and among environments was verified using the Scott Knott's method of clustering of means (P <0.05). For the study of adaptability and stability, the methods of analysis of Eberhart and Russell and AMMI were used. Genotypes had the best performance of genetic potential in 2010/11 crop year. The best group in Bom Jesus-PI consisted of 16 genotypes and had an average grain yield higher than 3181.61 kg ha-1, what is well above the global average grain yield (2108.26 kg ha-1). G5 and G9 genotypes were the ones with greater adaptability and stability in the three environments with high average grain yield (2362.5 kg ha-1). Therefore, the identification of genotypes presenting such behavior is important for recommending cultivation in the studied environments or in similar areas. It was possible to identify genotypes that have high grain yield and that are stable and adapted for cultivation in the Cerrado at Piauí state.
Keywords: AMMI; Eberhart & Russell; Genotype x environment interaction; Glycine max (L.) Merrill; Productive performance